Measuring the determinants of women’s empowerment in agricultural index in Bangladesh: application of the structural equation modeling approach - Sarma, Paresh Kumar; Alam, Mohammad Jahangir; Begum, Ismat Ara; Ethen, Dilshad Zahan; Yeasmin, Farzana; Crase, Lin; McKenzie, Andrew M. (Frontiers in Sustainable Food Systems, 2025)
The study investigates the determinants of women’s empowerment utilizing data from the Bangladesh Integrated Household Survey 2018, specifically through the construction of the Women’s Empowerment in Agriculture Index. Using structural equation modeling, it assesses how various indicators such as decision-making, freedom of mobility, access to agricultural extension services, group membership, and birth control decisions contribute to women’s empowerment outcomes. This index is based on decision-making regarding production, resources, income, leadership, time use, and gender parity sub-index. The study employs structural equation modeling to explore the association among key indicators of women’s empowerment, including decision-making, freedom of mobility, access to agricultural extension services, group membership, and birth control decisions. Our findings reveal that access to agricultural extension services, freedom of mobility, group membership, birth control decisions, and decision-making all exert significant direct effects on women’s empowerment in Bangladesh. The Women’s Empowerment in Agriculture Index itself is also significantly associated with these indicators, highlighting its role as a comprehensive measure. These results suggest that agricultural extension services can serve as a critical pathway to enhancing women’s empowerment. The research provides valuable insights for policymakers, donor agencies, academics, and extension workers to effectively allocate resources aimed at advancing women’s empowerment in developing countries like Bangladesh.